Dendrochronological studies in beech stands of the Skolivski Beskydy National Nature Park - Iryna M. Koval; Nadiya V. Maksymenko; Iryna M. Shpakivska (Наукові праці Лісівничої академії наук України)
The object of the study is the primary European beech forest in the Skolivski Beskydy National Nature Park. The subject of the study is the response of the radial increment of Fagus sylvatica L., to climate change. The paper aims to establish the relationships between the radial increment of beech and climatic factors in order to reveal the sensitivity of beech stands to climate change.